Interpreting survey questions about sexual aggression in cross-cultural research: A qualitative study with young adults from nine european Countries - Krahé, Barbara; De Haas, Stans; Vanwesenbeeck, Ine; Bianchi, Gabriel; Chliaoutakis, Joannes; Fuertes, Antonio; Gaspar, Margarida M.; Hadjigeorgiou, Eleni; Hellemans, Sabine; Kouta, Christiana; Meijnckens, Dwayne; Murauskiene, Liubove; et al. (My University, 2016)
Examining equivalence in the interpretation of survey items on sexual assault by participants from different cultures is an important step toward building a valid international knowledge base about the prevalence of sexual aggression among young adults. Referring to the theoretical framework of contextualism, this study presents qualitative data from semi-structured interviews with 128 young adults from nine EU countries on their understanding of survey items from the Sexual Aggression and Victimization Scale (SAV-S). The measure had previously been used to collect quantitative data on the prevalence of sexual aggression perpetration and victimization in the same countries that had yielded substantial differences in the rates of victimization and perpetration between countries. Based on the methodological approach of a mixed research design, the current study was conducted as a follow-up to the quantitative study with a new sample to explore whether systematic differences in the interpretation of the survey items in the different countries might explain part of the variation in prevalence rates. The interviews showed that participants from the nine countries interpreted the items of the SAV-S in a similar way and as intended by the authors of the scale. Systematic differences between men and women in interpreting the survey items were revealed. Implications of the findings for conducting survey research on sexual aggression across cultures are discussed.
Keywords: Cross-cultural; Gender; Interview study; Sexual aggression; Survey